Circuit Design of Digital Closed Loop Control System for FOG - Qiudong Sun; Yufeng Shao; Jiancun Zuo; Liandong Wang; Lin Gui (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Fiber optic gyroscope (FOG) is a new angular rate sensor based on the Sagnac effect. It has been widely applied in the navigation control system of aircrafts, spacecrafts and ships. But its stability, reliability and miniaturization are always the research focuses and difficulties. This paper presented a circuit design method for the digital closed loop control system of FOG based on FPGA. Based on a large number of experiments, this paper summarized the parameter demands for each module of closed loop control circuit and designed a corresponding circuit using FPGA. The proposed dual closed loop technique improved the zero offset stability of FOG. The using of FPGA brought the digital signal processing by software, the system reliability and agility enhancement as well as the system miniaturization. Particularly, we discussed the problems of component   selection and the anti-jamming measures for PCB design to improve the performances of the system. We also developed some samples of FOG using this design method. The experiments and tests show that the proposed method is efficient and valuable. The stabilities of zero-offsets of all samples are less than 0.075deg/h.